2018
DOI: 10.1038/s41419-018-1183-8
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA AC003092.1 promotes temozolomide chemosensitivity through miR-195/TFPI-2 signaling modulation in glioblastoma

Abstract: Temozolomide (TMZ) and radiation therapy combination for glioblastoma (GB) patients has been considered as the most effective therapy after surgical procedure. However, the overall clinical prognosis remains unsatisfactory due to intrinsic or developing resistance to TMZ. Recently, increasing evidence suggested that long noncoding RNAs (lncRNAs) play a critical role in various biological processes of tumors, and have been implicated in resistance to various drugs. However, the role of lncRNAs in TMZ resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 53 publications
2
40
0
Order By: Relevance
“…LncRNAs GAS5, NEAT1, GACAT3, CASC9, HMMR-AS1, LINC00152, HOTAIRM1, AC003092.1, HOXD-AS1, OIP5-AS1, DANCR and so on have been reported to play oncogenic or tumour suppressive roles in glioma. 32,33,[41][42][43][44][45][46][47][48][49] Our study further proved the critical roles of lncRNAs in glioma and provided another candidate lncRNA for glioma prognosis and therapy. Multi-centre analyses of the correlation between LINC00526 expression and prognosis of glioma patients would further detect the potential of LINC00526 as a prognostic biomarker, which needs further investigation.…”
Section: Discussionsupporting
confidence: 56%
“…LncRNAs GAS5, NEAT1, GACAT3, CASC9, HMMR-AS1, LINC00152, HOTAIRM1, AC003092.1, HOXD-AS1, OIP5-AS1, DANCR and so on have been reported to play oncogenic or tumour suppressive roles in glioma. 32,33,[41][42][43][44][45][46][47][48][49] Our study further proved the critical roles of lncRNAs in glioma and provided another candidate lncRNA for glioma prognosis and therapy. Multi-centre analyses of the correlation between LINC00526 expression and prognosis of glioma patients would further detect the potential of LINC00526 as a prognostic biomarker, which needs further investigation.…”
Section: Discussionsupporting
confidence: 56%
“…demonstrated that miR‐130a was subjected to epigenetic silencing in hemangioma, which consequently ameliorated the malignancy through targeting TFPI‐2 via the FAK/PI3K/Rac1/mdm2 signaling cascade. In addition, the study performed by Xu et al . showed that lncRNA AC003092.1 improved chemosensitivity to temozolomide by modulating the miR‐195/TFPI‐2 pathway in glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…As is known to all, in ceRNA mechanism, lncRNAs could competitively bind with miRNAs, thus positively regulating the target genes of miRNAs. [13][14][15] In these F I G U R E 3 F11-AS1 regulated PTEN expression by competitively binding with miR-3146. A, RT-qPCR of PTEN in cells transfected with miR-3146 mimics and miR-3146 mimics+pcDNA3.1/F11-AS1.…”
Section: F11-as1 Regulates Pten Expression By Competitively Bindingmentioning
confidence: 97%